Comparison of cardiac rehabilitation outcome measures - Hevey, David (Trinity College (Dublin, Ireland). School of Psychology, 2000)
The aim of the present study was to investigate the responsiveness of psychosocial instruments to cardiac rehabilitation intervention. Responsiveness refers to the ability of an instrument to detect change over time and it is a key component of evaluative instruments. The study comprised two main components: 1. a systematic review of the literature on psychosocial outcome after cardiac rehabilitation to identify those instruments with empirical evidence documenting their responsiveness to multifactorial cardiac rehabilitation intervention -- 2. a prospective study to examine the responsiveness of 9 psychosocial instruments to cardiac rehabilitation intervention in a sample of cardiac patients.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin